The Role of Magnetic Resonance Imaging for the Diagnosis of Atypical Parkinsonism - Chougar, Lydia; Pyatigorskaya, Nadya; Degos, Bertrand; Grabli, David; Lehéricy, Stéphane (Frontiers in Neurology, 2020)
The diagnosis of Parkinson’s disease and atypical parkinsonism based on clinical criteria remains limited, especially at early stages of the disease, as symptoms may often overlap. The development of multimodal MRI has dramatically improved the diagnostic accuracy as well as the understanding of the pathophysiology of parkinsonian syndromes. Structural and quantitative MRI sequences sensitive to several tissue properties are able to depict differential patterns of tissue alterations specific to each disease. Machine-learning-based differentiation of parkinsonian syndromes using MRI data has shown high performance, providing results at the individual level. Such approaches could be translated into a clinical environment and impact positively the management of parkinsonian patients. This review aims to summarize the different structural and quantitative MRI techniques and their contribution for the differential diagnosis of atypical parkinsonian syndromes at the patient level and in a research setting.